AI for Sustainable Soil Health: Predicting Nutrient Deficiencies & Recommendations - Phapale, Anuja; Shiledar, Aditya (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
In modern agriculture, maintaining soil health is more important than sustainable crops. This paper presents an AI-driven approach to soil health management, focusing on predicting nutrient deficiencies and recommending sustainable actions Using machine learning techniques, we the system analyzes soil data to assess health status and identify nutrient imbalances. The AI ​​system provides personalized recommendations to farmers, including strategies such as crop targeting and crop rotation. Through experiments and case studies, we demonstrate the effectiveness of our approach in increasing soil fertility and promoting sustainable agricultural practices.